Persistent organic pollutants in great skuas Stercorarius skua - Leat, Eliza Helen Kelsey (2013)
The bioaccumulation of persistent organic pollutants (POPs) is of particular environmental concern in top predators, which accumulate high concentrations of POPs that can cause adverse effects. Previous small scale studies found high concentrations of POPs in adult great skuas, Stercorarius skua, a top predator in the marine environment. This thesis investigates the factors affecting concentrations and patterns of POPs (contribution of individual POPs to the ΣPOPs) in the great skua across its breeding range in the north-east Atlantic. Clear differences between colonies in both concentration and pattern of POPs in adult plasma were not indicative of being caused by long range transport of POPs in the atmosphere. Variation in diet between colonies is the mostly likely explanation for these colony differences, with great skuas from some colonies having a greater proportion of fish in their diet whilst others eat more seabird prey. Although seabirds are often used in studies of POPs in the environment, the effect of migratory behaviour has not previously been studied in detail. By using a combination of global location sensor (GLS) loggers and feather stable isotopes from winter grown feathers, the wintering areas of individuals from three breeding populations of great skuas were identified. Great skuas spend the winter in three distinct areas across the North Atlantic, with birds from the same breeding colonies wintering in different areas. In two of the three breeding populations, wintering area explained a significant proportion of variation in organochlorines (OCs) concentrations and pattern. However in the colony with the highest concentrations of OCs, no effect of wintering area was found, possibly as a result of these great skuas feeding at a higher trophic level during the breeding season than other populations. Temporally, concentrations of OCs were higher in 1980 than 2008 in eggs, whilst newer contaminants polybrominated diphenyl ethers (PBDEs) and perfluorinated chemicals (PFASs) show the opposite ...